2018
DOI: 10.1101/327767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First report and multilocus genotyping of Enterocytozoon bieneusi from Tibetan pigs in southwestern China

Abstract: 24Enterocytozoon bieneusi is a common intestinal pathogen and a major cause of 25 diarrhea and enteric diseases in a variety of animals. While the E. bieneusi genotype 26 has become better-known, there are few reports on its prevalence in the Tibetan pig. 27 This study investigated the prevalence, genetic diversity, and zoonotic potential of E. 28 bieneusi in the Tibetan pig in southwestern China. Tibetan pig feces (266 samples) 29 were collected from three sites in the southwest of China. Feces were … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Although high infection rates were observed in 1–2 year-old pigs (41.51%, 22/53) and 0–1 year-olds (33.33%, 61/183), these rates were not significantly different ( χ 2 = 1.240, df = 1, p > 0.05). The results of the present paper were previously published as a preprint [26]. With an overall infection rate of 31.2%, this rate is lower than the documented prevalence of E. bieneusi for wild boars in Sichuan province, China (41.2%), pigs in Henan province, China (45.5%), wild boars in central Europe (33.3%), and pigs in the State of Rio de Janeiro, Brazil (59.3%) [10, 24, 28, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Although high infection rates were observed in 1–2 year-old pigs (41.51%, 22/53) and 0–1 year-olds (33.33%, 61/183), these rates were not significantly different ( χ 2 = 1.240, df = 1, p > 0.05). The results of the present paper were previously published as a preprint [26]. With an overall infection rate of 31.2%, this rate is lower than the documented prevalence of E. bieneusi for wild boars in Sichuan province, China (41.2%), pigs in Henan province, China (45.5%), wild boars in central Europe (33.3%), and pigs in the State of Rio de Janeiro, Brazil (59.3%) [10, 24, 28, 46].…”
Section: Resultsmentioning
confidence: 99%
“…Multilocus sequence typing (MLST) based on sequence analysis of four markers (MS1, MS3, MS4 and MS7) with simple tandem repeats and the ITS has been used in investigating the transmission dynamics of E. bieneusi in humans and some animals, including pigs, sheep, rabbits, calves, black bears, giant pandas and horses [27][28][29][30][31][32][33][34][35]. Thus far, only three studies have used the MLST analysis to characterize E. bieneusi isolates in NHPs, and only one study has found the presence of an overall clonal population structure and an epidemic population structure in subpopulations of this pathogen in NHPs [11,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that pigs can be infected with microsporidia spores at an early age, consequently the animals excrete spores throughout their lives which can contaminate the environment (Sak et al., 2008). Therefore, using untreated pig manure as fertilizer that may be a potential source of infection in humans and animal population, which in turn can be a risk to public health (Zhao et al., 2014, Luo et al., 2019). In many countries of the world, pigs are the major sources of meat production (Dione et al., 2017, Tisdell, 2013).…”
Section: Introductionmentioning
confidence: 99%